Model Pembelajaran Sosial Pada Pembelajaran PAI Online Learning Dimasa Pandemi Di SMA - Indry Delvytra; Riska Yulia Sari (Journal of Pedagogy and Online Learning, 2023)
This study aims to examine how the implementation of the social learning model, namely Jurisprudence, in PAI subjects in high school. With the learning situation conducted online, a strategy is needed by the teacher in choosing the method in the learning activities to be carried out. The jurisprudential model emphasizes the relationship between individuals and society or other people. The research method used is descriptive qualitative. By using this descriptive method, researchers collect data through literature studies such as journals, articles and other scientific works. In descriptive qualitative research, the basis for analysis is the dynamic interplay of the issues raised, theories, experiences, conversations, and reflections. From this research, the syntax of the social learning model in schools will be found.